The Influence of Caused-Related Marketing on Consumer Buying Interest: An Environmental Care Campaign on Skincare Products in Indonesia - Andreas Tulus Monang; Muhammad Hendra Maulana; Faranita Mustikasari (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of Cause-Related Marketing (CRM) on consumer buying interest in skincare products in Indonesia, especially through environmental care campaigns. With increasing public awareness of sustainability issues, skincare companies are competing to adopt marketing strategies that focus on social and environmental responsibility. This study uses a quantitative approach with an online survey method of 104 male respondents who use skincare products. The analysis was carried out using a reflective measurement model to test the relationship between variables such as Cause Participation, Congruence between Product and Cause, Attitude Toward the Cause, Willingness to Pay More, and Purchase Intention. The results of the study show that Cause Participation has a significant positive influence on Attitude Toward the Cause and Purchase Intention. Similarly, Attitude Toward the Cause has a positive effect on Willingness to Pay More and Purchase Intention. However, Congruence between Product and Cause has no significant effect on Purchase Intent. These findings confirm that consumer involvement in environmental care campaigns plays a greater role in building purchase intent than the match between the product and the cause carried. The practical implications of this study provide insights for skincare companies to optimize environmental campaigns as an effective and sustainable marketing strategy.